A Chronic Rash: Why We Should Ask About Body Art. Issue 2 (March 2016) - Sandhu, Amandeep; Thyssen, Jacob P.; Jacob, Sharon E.
Abstract : ABSTRACT: Allergic reactions have infrequently been reported to metals found in tattoos (e.g., chromium, mercury). We report inflammation in a blue ink tattoo, associated with a positive patch test reaction to cobalt chloride, likely indicating primary sensitization to cobalt.